Analyzing teacher-developed modules in the Kurikulum Merdeka for senior high schools - Atikah Wati; Natalia Anggrarini; Ela Meilisari (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
One of the key elements of the Kurikulum Merdeka is the transformation of traditional lesson plans into teaching modules. However, many teachers face difficulties in compiling these modules effectively. This study aims to analyze teacher-developed instructional modules and identify the challenges encountered during their development. Employing a qualitative case study design, data were collected through documentation analysis and interviews with four English teachers at senior high schools implementing the Kurikulum Merdeka. The findings reveal that several module components were incomplete, poorly described, or misunderstood by teachers, although most criteria outlined in the curriculum were technically fulfilled. Key challenges included unfamiliarity with new module components and terminology, limited insight into students’ prior English proficiency, insufficient training, inadequate reference materials, and a lack of supporting facilities. These obstacles, if persistent, may undermine the curriculum’s effectiveness. This study contributes practical insights by highlighting context-specific implementation barriers, emphasizing the urgent need for sustained teacher training and institutional support to strengthen module development and ensure successful curriculum integration. Keywords: Teaching module; Teachers’ Challenges; Kurikulum Merdeka